As estratégias de renda dos agricultores familiares de Itapejara d’Oeste nos anos 2005 e 2010 - Villwock, Ana Paula Schervinski (2015)
The process of commodification, that is, the growing direction of activities for the market, turned the characteristics of social reproduction of family farmers, especially in the way we produce and earn income. Knowing that the market may aggravate rural poverty as, on the other hand, create new opportunities, social reproduction of modern family farming very apparent by its adaptability that allows diversify its sources of farm and non-farm income. So we ask: what are the combinations of activities of family farmers of Itapejara d'Oeste in the years 2005 and 2010 which resulted in higher income? Therefore, the general purpose of this work is to analyze the income strategies of family farmers of Itapejara d'Oeste which enabled it to overcome poverty in the years 2005 and 2010. As a result identified in families that belong to the high income category: (1 ) deepening the commercialization process; (2) investments in technology in family production units, especially in those who composed the income in the production of grains and milk binomial (3) the increased availability of total labor force and land area; (4) the diversification of the total income from non-agricultural income in family production unit.